(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
This text focuses on the analysis of the cadaveric examinations present in police inquiries involving suicides, dating from 1912 to 1928, in São João do Triunfo, in the southeastern part of Paraná. When dealing with the interior of Paraná in the early twentieth century, the forensic work was not always carried out by professional experts. So, the aim is to understand the ways in which the bodies were examined and narrated by "common people" disguised as authorities. For this proposal, we will use references from the historiography of violence and Foucault’ categories.